ANALISIS PEMBANGUNAN SUMBER DAYA MANUSIA DAN PERTUMBUHAN EKONOMI : STUDI PENGARUH INVESTASI, TENAGA KERJA, RATA-RATA LAMA SEKOLAH, DAN PENGELUARAN PEMERINTAH UNTUK PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI PROVINSI - PROVINSI DI INDONESIA PERIODE 1 - Tete Saepudin (Indonesian Journal of Economics and Business, 2011)
This research  purpose  main to knowing and analyzing ; influence  of invesment (capital) growth, labor skills growth, labor unskills growth, education attainment  and  budget education expenditure growth  to economic growth.            The research uses descriptive and verificative,  with using method pool least sequares. The using data is secondary data in the form of pooled-data which  is a combination of time series  and cross-section data of 26 provinces in Indonesia priod 1994-2008.            The result of this study  shows that (1) the  influence of capital (invesment) growth have on positif effect and signifikan to economic growth, (2) the influences of the labor skills growth have on negative  effect and not significan to economic growth, (3) the influences of the labor unskills have on positif effect and  significan to economic growth, (4) the influences of the education attainment have on positif effect and significant to economic growth, (5) the influences of the budget education expenditure growth have on positif effect and significan to economic growth the provinces in Indonesia.